Pengaruh Total Quality Management (TQM) terhadap Kinerja Keuangan dengan Kualitas Kinerja Pegawai sebagai Variabel Moderasi pada PT. Bank Pembangunan Daerah Bali di Buleleng - Apriana, Kadek Vina Ary; I Putu Hendra Martadinata (Universitas Pendidikan Ganesha, 2024)
This research aims to determine the effect of Total Quality Management (TQM) on Financial Performance with Employee Performance Quality as a Moderating Variable at PT. Bali Regional Development Bank in Buleleng. This research is quantitative research using primary data obtained from questionnaires and measured using a Likert scale. The population in this study were all BPD employees in Buleleng. The sampling technique in this research used a purposive sampling method. Using a sample with a total of 96 respondents. Data analysis in this research uses descriptive analysis, data quality testing, classical assumption testing, multiple linear regression analysis and hypothesis testing with the help of the PLS program. The results of this research show that: (1) Total Quality Management (TQM) has a significant positive effect on financial performance and (2) The quality of employee performance can moderate the effect of Total Quality Management (TQM) on financial performance in a significantly positive way.